BUFFALO LIVESTOCK AND PRODUCTS IN EUROPE - Borghese, Antonio (Proceeding Buffalo International Conference, 2013)
Buffalo livestock and strategies are reported for all the countries in Europe, where buffalo specie is reared and used for food production, as Italy, Romania, Bulgaria, Germany, Macedonia, United Kingdome, Greece, Serbia, Albania, Ukraine, Hungary. Particularly Italy situation is discussed as in this country selection, milk recording and production, management, nutrition and reproduction techniques, quality food and marketing are really developed at top level. In Italy 50,000 buffaloes are recorded every month during the lactation, showing a milk yield of 2,220 kg in 270 days of lactation with 8.4% fat and 4.6% protein, as many champions produce more than 5,000 kg for lactation. Artificial insemination is largely applied. The National Association ofÂ Italian Buffalo breeders was instituted on 1979, the Buffalo Genealogical Book for the Mediterranean Italian Buffalo Breed on 1980, the famous mozzarella cheese obtained the Denomination Origin Protected on 1993, with Decree of Agricultural Ministry, approved by European Union, where milk and mozzarella characteristics are defined for consumer guarantee. In Italy 400,000 buffaloes are managed and fed in intensive system: the females are kept loose in paddock and mechanically milked twice a day; the males are managed in feed-lots or on slatted floor stables for fattening and are slaughtered at 15 months, achieving more than 400 kg live weight. Even if many productsÂ are appreciated coming from milk, as ricotta, provola, scamorza, treccia and other cheeses, or coming from meat, as steaks, roast, ham, bresaola, salami, the most important product in the Italian and international market is mozzarella, of which 36,000 tons are produced every year, with a value of 500 million euros. The consumption is 82% in Italy, 18% for export, particularly for Germany, France, USA, UK.